Where internal medical patients receive intensive interventions: results from a tertiary-care hospital in Israel - Gideon Leibner; Shuli Brammli-Greenberg; David Katz; Yaakov Esayag; Nechama Kaufman; Adam J. Rose (BMC, 2023)
Abstract Background Patients admitted to internal medicine may be moved to more advanced-care settings when their condition deteriorates. In these advanced care settings, there may be higher levels of monitoring and greater ability to deliver Intensive Medical Treatments (IMTs). To the best of our knowledge, no previous study has examined the proportion of patients at different levels of care who receive different types of IMTs. Methods In this retrospective observational cohort study, we examined data from 56,002 internal medicine hospitalizations at Shaare Zedek Medical Center, between 01.01.2016 and 31.12.2019. Patients were divided according to where they received care: general-ward, Intermediate-Care Unit, Intensive Care Unit (ICU), or both (Intermediate-Care and ICU). We examined the rates at which these different groups of patients received one or more of the following IMTs: mechanical ventilation, daytime bi-level positive airway pressure (BiPAP), or vasopressor therapy. Results Most IMTs were delivered in a general-ward setting - ranging from 45.9% of IMT-treated hospitalizations involving combined mechanical ventilation and vasopressor therapy to as high as 87.4% of IMT-treated hospitalizations involving daytime BiPAP. Compared to ICU patients, Intermediate-Care Unit patients were older (mean age 75.1 vs 69.1, p < 0.001 for this and all other comparisons presented here), had longer hospitalizations (21.3 vs 14.5 days), and were more likely to die in-hospital (22% vs 12%). They were also more likely to receive most of the IMTs compared to ICU patients. For example, 9.7% of Intermediate-Care Unit patients received vasopressors, compared to 5.5% of ICU patients. Conclusion In this study, most of the patients who received IMTs actually received them in a general-bed and not in a dedicated unit. These results imply that IMTs are predominantly delivered in unmonitored settings, and suggest an opportunity to re-examine where and how IMTs are given. In terms of health policy, these findings suggest a need to further examine the setting and patterns of intensive interventions, as well as a need to increase the number of beds dedicated to delivering intensive interventions.